Crude Palm Oil Corruption: A Discourse on the Imposition of Capital Punishment - Camila, Dwi; Syamsu, Andi Pramudya; Firdaus, Ayi Dudi; Norzulaika, Siti; Binti Sulaiman, Wan Nurainun Najwa (Universitas Muhammadiyah Yogyakarta, 2022)
The study aims to discuss on the corruption of Crude Palm Oil (CPO) export cases that have led to the scarcity of cooking oil at affordable prices in Indonesia. It is harmful for the public as the Crude Palm Oil (CPO) has been exported without a permit and does not meet the requirements of Domestic Market Obligation (DMO) and Domestic Price Obligation (DPO). The study is a normative legal research employing descriptive-qualitative upon data collected through a library study. The study shows that the case of crude palm oil (CPO) export corruption made the supply of cooking oil disrupted that led to economic and political instability. In response to this, the government conducted an investigation and found several suspects of corruption cases. While the legal process running, the discourse on the application of death penalty arose within the society. It was so because this corruption occurred during the pandemic. However, the use of the capital punishment in cases of corruption is restricted because it can only be used in specified circumstances, especially when the funds are intended for dealing with dangerous situations, national natural disasters, social unrest, economic and monetary problems, and corruption repetition.